Graphite oxide-driven miscibility in PVDF/PMMA blends: Assessment through dynamic rheology method. (November 2017) - Liu, Danfeng; Li, Wei; Zhang, Nan; Huang, Ting; Yang, Jinghui; Wang, Yong
Graphical abstract: Highlights: It is a novel work to evaluate the effects of Graphite Oxide on PVDF/PMMA blends. Phase diagrams of PVDF/PMMA/Graphite Oxide composites were achieved. Selective adsorption and resultant molecular entanglement were explored. Abstract: The phase behaviors involving the phase fluctuation in melt of poly(vinylidene fluoride) (PVDF)/poly(methyl methacrylate) (PMMA) blends with varying graphite oxide concentration were investigated through dynamic rheological measurement. The phase diagrams of the blends with different concentration of graphite oxide were achieved through dynamic temperature and frequency sweep, showing the incorporation of graphite oxide would shift up the phase diagram of PVDF/PMMA blends and enlarge the miscibility window of the blends. Dynamic time sweep was applied to track the phase separation process, which exhibited that graphite oxide can slow down the phase separation process. The underlying mechanism for graphite oxide-driven miscibility in PVDF/PMMA blends was explored via evaluating the molecular entanglement of PVDF/PMMA/Graphite Oxide ternary composites. The interfacial tensions showed the selective adsorption of PMMA on graphite oxide, which was responsible for the role of graphite oxide as entanglement points. And it was found the increase of graphite oxide concentration could lead to higher entanglement density. Therefore, it can be concluded that the graphite oxide can act as entanglement point, further to stabilize the phase structure and to slow down the phase separation. This work serves as an experimental verification to enrich the thermodynamic and kinetic investigations on phase behaviors of particle-filled miscible blends; furthermore new insights are produced and provided to tailor the phase morphology of miscible blends via incorporation of particles.